Assessment of interobserver concordance in polysomnography scoring of sleep bruxism() - Ferraz, Otávio (Sleep Sci, 2015)
INTRODUCTION: Objective evaluation of sleep bruxism (SB) using whole-night polysomnography (PSG) is relevant for diagnostic confirmation. Nevertheless, the PSG electromyogram (EMG) scoring may give rise to controversy, particularly when audiovisual monitoring is not performed. Therefore, the present study assessed the concordance between two independent scorers to visual SB on a PSG performed without audiovisual monitoring. METHODS: Fifty-six PSG tests were scored from individuals with clinical history and polysomnography criteria of SB. In addition to the protocol of conventional whole-night PSG, electrodes were also placed bilaterally on the masseter and temporal muscles. Visual EMG scoring without audio video monitoring was scored by two independent scorers (Dentist 1 and Dentist 2) according the recommendations formulated in the AASM manual (2007). Kendall Tau correlation was used to assess interobserver concordance relative to variables “total duration of events (seconds), “shortest events”, “longest events” and index in each phasic, tonic or mixed event. RESULTS: The correlation was positive and significant relative to all the investigated variables, being T>0.54. CONCLUSION: It was found a good inter-examiner concordance rate in SB scoring in absence of audio video monitoring.